2022
DOI: 10.1021/acsami.2c07319
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Laser-Ablated Bioinspired Hydrogel-Based Porous Gating System for Sustained Drug Release

Abstract: Gating systems have been extensively researched in energy harvesting, lab-on-chip applications, and so forth. However, the controlled drug delivery system with artificial hydrogel-based porous gating systems (HPGSs) is rarely reported. Herein, a biomimetic HPGS with a pH-responsive hydrogel as the valve and polydimethylsiloxane as the frame is fabricated by in situ femtosecond laser microdrilling and subsequent ultraviolet exposure. The proposed HPGS loaded with doxorubicin hydrochloride (DOX) is stable under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Zhang et al fabricated a biomimetic hydrogel-based porous gating system through FsLDW-based microdrilling and subsequent ultraviolet exposure, which consisted of a pH-sensitive hydrogelbased valve and a frame made of PDMS. The proposed gating systems, including membrane and microcapsule systems inspired by plant stomata, could realize a reversible transition between 'OFF' and 'ON' states based on pH-triggered valve expansion or contraction, which could be applied to realize sustained drug release and on-demand tumor cells treatment (figures 15(d) and (e)) [56]. Achieving precise drug delivery is a paramount objective in targeted therapy, but it poses significant challenges.…”
Section: Biomedical Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al fabricated a biomimetic hydrogel-based porous gating system through FsLDW-based microdrilling and subsequent ultraviolet exposure, which consisted of a pH-sensitive hydrogelbased valve and a frame made of PDMS. The proposed gating systems, including membrane and microcapsule systems inspired by plant stomata, could realize a reversible transition between 'OFF' and 'ON' states based on pH-triggered valve expansion or contraction, which could be applied to realize sustained drug release and on-demand tumor cells treatment (figures 15(d) and (e)) [56]. Achieving precise drug delivery is a paramount objective in targeted therapy, but it poses significant challenges.…”
Section: Biomedical Engineeringmentioning
confidence: 99%
“…The ultrashort pulse duration and immensely high peak intensity of femtosecond laser bring unprecedented physical conditions for modern extreme manufacturing and scientific experimental research [42][43][44][45][46][47][48]. FsLDW technology can promote the flexible and efficient manufacturing of well-designed structures with on-demand stimulus-responsive behaviors, thus further facilitating current tendencies of miniaturization, functionalization, integration, and ultimate practical application of these intelligent structures in diverse fields such as microfluidics [49][50][51], optics [52][53][54], robotics [55], and biomedical engineering [10,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…The on-demand control of microfluids (droplets or bubbles) utilizing specific functional structures and materials [1,2] is fundamental to diverse scientific research and industrial processes, such as water-fog harvesting, [3] lab on a chip, [4] gas-liquid interfacial biochemical reaction, [5] oil-water separation, [6][7][8][9] permeable membrane/gating, [10,11] sustained drug release, [12] air purification, [13] froth management, [14] and others. Compared DOI: 10.1002/admt.202300267 with droplet manipulation, bubble control has been proven to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Porous polymers with many functional groups have attracted attention due to their wide applications as catalyst supports, as adsorbents, as tissue scaffolds, and in controlled drug release [ 1 , 2 , 3 ]. So far, various methods have been applied to prepare porous macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solvents can be replaced by CO 2 because the latter is abundant, nontoxic, nonflammable, and readily available; thus, it should be deeply utilized [10]. Cooper et al reported poly(vinyl alcohol) hydrogel obtained from a CO 2 -in-water (C/W) emulsion template; the gel had a bulk density of 0.043 g/cm 3 , which could be useful in biomedical applications [11]. In our previous studies, UiO-66 and HKUST-1 were applicable as key emulsion stabilizers to stabilize C/W HIPEs, and the resulting composite gel had good adsorption and hydrophilicity, while the mechanical properties of the material were improved, e.g., resilience [12,13].…”
Section: Introductionmentioning
confidence: 99%